Exploring Gender Diversity in IT and CS Departments Within 3 Private Universities in Erbil City. (18th October 2019) - Abulrahman, Mohammad Salim; Khalilov, Savriddin
The number of information technology (IT) jobs is increasing dramatically in Iraq. This has produced an increased need for IT graduates than before. On the other hand, most IT and computer science (CS) departments in private universities are seeing small numbers of females in their courses. This indicates that these private universities have failed in attracting a sufficient percentage of female students. In this article, we explore the gender gap in IT and CS departments at 3 private universities: Tishk, Cihan, and Bayan, using 3 data sets related to the 2017 to 2018 academic year. The research design is descriptive and primary data were collected using personal observations made by the authors over the past 2 years. By analyzing these data sets, we can discover important issues such as students' diversity in computing departments. For example, we find that a gender gap does not clearly exist in the IT department of Tishk University, while it's more obvious in CS departments of Bayan and Cihan Universities. This finding implies that there is a need for some initiatives to attract women to IT and CS departments and to more investigate the gender gap in computing within the higher education level. These findings may also be relevant to the computing programs at other large public universities.